Primary retroperitoneal schwannoma. Case presentation - Annia Rivacoba Betancourt; Yusnier Varona Varona; Javier Cruz Batista (Medisur)
Schwannoma are soft tissue tumors that originate in Schwann cells of the nerve sheath in peripheral, cranial or visceral nerves, anywhere in the body. This is an extremely unusual entity. The article describes the case of a 47-years-old black-skinned patient with a history of health who attended a triage consultation, reporting that one month ago he had started having difficulty urinating, leading to acute urinary retention. The physical examination confirmed, through digital rectal examination, a tonic sphincter, an empty rectal ampulla, a grade IV enlarged prostate with a fibromuscular consistency with a smooth and mobile surface; not painful. After carrying out imaging and complementary studies, he received surgical treatment at the María Curie Provincial Oncological Teaching Hospital, in Camagüey, Cuba. He was diagnosed with a retroperitoneal schwannoma, confirmed by the Pathology report. Currently the evolution of the patient is positive, without medical treatment, but with periodic follow-up.